Goodness of Fit Tests and Power Comparisons for Weighted Gamma Distribution - Neetu Singla; Kanchan Jain; Suresh Kumar Sharma (Revstat Statistical Journal, 2016)
In this paper, a weighted version of Gamma distribution known as Weighted Gamma (WG) distribution has been considered. Various tests of goodness of fit viz Kolmogorov–Smirnov, Cram´er–von Mises and Anderson–Darling have been applied to this family. Monte Carlo simulations have been carried out for power calculations. The powers of these tests have been compared which helps in ranking of these goodness of fit tests.